Identidade e consciência histórica : um estudo com professores de História que atuam na Educação de Jovens e Adultos – Paraná - Bonete, Wilian Junior (2019)
This work analyzes the process of constructing the identity and historical awareness of a group of 5 (five) History teachers who work in the Education of Young and Adults (EYA) in the public education network of the State of Paraná. We seek to understand how teachers attribute meaning to their academic trajectories and experiences, their entrance into teaching, their experiences in teaching history and the relationships they establish with the historical culture of society. We use an approach based on the Theory of History, allied to the presuppositions derived from History Teaching and Didactic of History. The main concepts used were those of identity, historical culture and historical consciousness proposed by Jörn Rüsen, Klaus Bergman and Claude Dubar, and school culture outlined by André Chervel and Dominique Julia. We worked on the concept of Didactics of History articulated to the teaching of History from the discussions of authors such as Nicole Tutiaux-Guillon, Sylvie Lalagüe-Dulac, Kátia Abud and Bodo Von Borries. On the empirical side, we developed an Information Collection Instrument with several questions about general data and formation and also a semi-structured script for oral interviews. For the categorization of the narratives, we made use of the textual analysis technique called Content Analysis proposed by Lawrence Bardin. The general result pointed out that the identity and historical consciousness of teachers is a daily construction that emerges from the intertwining of the different spaces of formation and performance, as well as the relations established with the historical knowledge produced in society.